PILOT STUDY OF A MEDICATION CHANGE TEACHING TOOL AND PHARMACIST DISCHARGE RECONCILIATION ON LIMITING MEDICATION ERRORS FOR HEART FAILURE PATIENTS. Issue 12 (18th November 2016) - Nicolsen, Erika; Markle, Jennifer; Curran, Lisa; Cooper, Julie; Bensimhon, Daniel
Abstract : Background: Hospital discharge frequently leads to medication changes for patients. The lack of standard methods to teach patients to make medication changes at home may contribute to the Centers for Medicare and Medicaid Services statistic that one in five patients discharged from the hospital suffers an adverse event, 72% of which are medication-related. Objectives: The purpose of this project was to evaluate the impact of a standardized pharmacist-led discharge medication reconciliation (MR) program and a home "Make Your Medication Changes" education tool on 30-day readmission rates due to preventable medication misadventures and HCAPS communication about medications scores. Methods: A lean rapid improvement event identified non-standardized methods for discharge MR. A 5-month prospective, single center pilot study was designed to evaluate the impact of standardized pharmacist led MR and discharge education tool compared with a retrospective cohort of readmitted heart failure (HF) patients using both pre- and post- and process control analyses. A picture education tool "Make Your Medication Changes" (figure 1), was developed and tested. Results: A significant reduction in 30-day readmissions related to preventable medication misadventures from 40% to 3% (p=0.0076) was observed. Process control analysis of readmissions due to preventable medication misadventures and HCAPS communication about medications scores suggests a pattern of improved outcomes over time (figure 2). Conclusions: Based on this pilot further study of standard methods for MR including a pharmacist role and medication change teaching tool are warranted for the potential to durably impact outcomes for HF patients at hospital discharge.Figure 1 Figure 2